Management of software engineering. (1st January 1999) - Middleton, Peter
This paper examines the efficiency and effectiveness of a prescriptive systems development methodology in practice. The UK Government's mandatory Structured Systems Analysis and Design Method (SSADM) was examined to determine its value to software projects. The evidence was collected from interviews with 17 project managers, discussions with participants on 3 large SSADM projects and from observing 90 end users in training. The conclusions are that prescriptive information systems methodologies are unlikely to cope well with strategic uncertainty, user communication or staff development. The recommendations are to focus more on soft organisational issues and to use approaches tailored to each project.